Fabrication of a novel dye sensitized solar cell by using organic bye from dragon fruit and spinach chlorophyll extract - Syafinar, Ramli (Macao Innnovation & Invention Association, 2014)
Macau International Innovation & Invention Expo 2013 (IIEX), 28th June - 30th June 2013 organized by Macao Innnovation & Invention Association at Macau Fisherman Wharf Exhibition Centre, China.